Early health economic evaluation of the future potential of next generation artificial vision systems for treating blindness in Germany - Bjoern Schwander (Health Economics Review, 2014)
The next generation of artificial vision devices (AVDs), which is currently developed in pre-clinical settings, has the potential to improve the vision of blind patients with retinitis pigmentosa (RP) in a manner that they will be categorized as visual impaired but no more as blind. This unprecedented vision improvement will result in a mentionable quality of life gain which poses the question at which costs the next generation AVDs are to be regarded as cost-effective, from a German healthcare payer perspective. In order to answer this research question a Markov model was developed to simulate and to compare the costs and effects of next generation AVDs versus best supportive care (BSC). Applying the base case settings resulted in incremental costs of exteuro107,925, in 2.03 incremental quality-adjusted life years (QALYs) and in a cost-effectiveness ratio of exteuro53,165 per QALY gained. Probabilistic and deterministic sensitivity analyses as well as scenario analyses for the effect size and the AVD costs were performed in order to investigate the robustness of results. In these scenario analyses a strong variation of the cost-effectiveness results was obtained ranging from exteuro23,512 (best case) to exteuro176,958 (worst case) per QALY gained by AVD therapy. This early health economic evaluation has to handle with three main uncertainty factors: the effect size of next generation AVDs, the costs of next generation AVDs and the WTP threshold that might be applied in RP patients, which reflect the main limitations of the presented assessment. In conclusion the presented early cost-effectiveness evaluation has obtained that next generation AVDs have the potential to be a cost-effective therapy option in patients with RP in Germany. The innovative nature, the high unmet medical need and the expected unprecedented efficacy of next generation AVDs will highly likely lead to the case that even relatively high incremental cost-effectiveness ratios, that have been obtained when simulating various effect and pricing scenarios, will be regarded as acceptable from a German healthcare payer perspective.
Keywords: 330; Cost-effectiveness; Early economic evaluation; Germany; Retinitis pigmentosa; Blindness; Medical devices; Artificial vision; Markov model; Health care payer perspective